2021
DOI: 10.1021/acsaem.1c01531
|View full text |Cite
|
Sign up to set email alerts
|

Hole-Transport-Underlayer-Induced Crystallization Management of Two-Dimensional Perovskites for High-Performance Inverted Solar Cells

Abstract: Currently, intensive research is being conducted on Ruddlesden–Popper-type two-dimensional (2D) perovskite-based solar cells because of the advantages such as excellent power conversion efficiency (PCE) and desirable environmental stability. A well-crystallized perovskite film plays a very important role in enhancing the performance of perovskite solar cells (PSCs). In this study, we investigated the effect of the wetting property of the underlying hole-transport layer (HTL) on the crystallization of 2D perovs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…The surface hydrophobicity and hydrophilicity of the hole contact have significant impacts on the perovskite film formation and perovskite crystal growth . On the premise of good wetting for perovskite precursor solution, high hydrophobicity of the hole contact is more likely beneficial to achieving large perovskite grains with less grain boundaries, and more perovskite nuclei with small perovskite grain sizes and a large amount of grain boundaries easily form on the substrate surface with high hydrophilicity. , On the other hand, it was found that the highly hydrophobic surface with a water contact angle >100° fails to facilitate the perovskite wetting and deposition . Hence, it is important to optimize the surface hydrophobicity and hydrophilicity.…”
Section: Resultsmentioning
confidence: 99%
“…The surface hydrophobicity and hydrophilicity of the hole contact have significant impacts on the perovskite film formation and perovskite crystal growth . On the premise of good wetting for perovskite precursor solution, high hydrophobicity of the hole contact is more likely beneficial to achieving large perovskite grains with less grain boundaries, and more perovskite nuclei with small perovskite grain sizes and a large amount of grain boundaries easily form on the substrate surface with high hydrophilicity. , On the other hand, it was found that the highly hydrophobic surface with a water contact angle >100° fails to facilitate the perovskite wetting and deposition . Hence, it is important to optimize the surface hydrophobicity and hydrophilicity.…”
Section: Resultsmentioning
confidence: 99%
“…22 The cross-point of the ohmic and TFL regimes is known as the trap-filled limit voltage (V TFL ), which is determined by the trap states. 37 Hence, the trap density (n trap ) of the devices can be calculated from the following eqn (1):…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21] The mismatch between the polarity leads to high contact angles and severe wetting issues of perovskite solution on the hydrophobic HTLs and thus results in poor surface coverage, pinholes, high charge carrier recombination, low open-circuit voltage (V OC ), and device performance. [10,[22][23][24] In addition to hydrophobic polymeric HTLs, recently, carbazole-based self-assembled monolayers (SAMs) with phosphonic acid anchoring groups such as [2-(9H-Carbazol-9-yl)ethyl]phosphonic acid (2PACz), [2-(3,6-dimethoxy-9H-carbazol-9-yl)ethyl]phosphonic acid (MeO-2PACz), and [4-(3,6-Dimethyl-9H-carbazol-9-yl)butyl]phosphonic acid (Me-4PACz) have been in the limelight because of their better energy level alignment with some of the most relevant perovskite compositions with high device efficiencies. [25][26][27][28][29][30] In particular, Me-4PACz-based perovskite solar cells showed one of the highest efficiency for p-i-n-type devices both in single junction and tandem (with silicon) configurations.…”
Section: Introductionmentioning
confidence: 99%